2014
DOI: 10.1007/s12010-013-0701-5
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Perfluorodecalin Application for In Situ Extraction and Enhanced Naphthoquinones Production in Arnebia euchroma Cell Suspension Cultures

Abstract: Suspension cultures of Arnebia euchroma supported with liquid perfluorodecalin (PFD) degassed, aerated, or ethylene-saturated were investigated as a novel in situ extraction system for enhanced alkannin/shikonin production. Simultaneously, the effect of PFD applied as the liquid gas carrier on the growth of A. euchroma biomass was studied. The similar dry (4-fold) and fresh (7-fold) biomass increase was observed in the control (without PFD addition) and supplemented with PFD-degassed or PFD-aerated cultures wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 29 publications
0
18
0
3
Order By: Relevance
“…The results obtained in previous research performed by our group indicated that direct application of PFD to the culture system constitutes simple and efficient conditions for the enhancement of secondary metabolites production (Sykłowska-Baranek et al 2014, 2015a. In cultures of KT root line supplemented with PFD-aerated or degassed but without elicitors no lignan content was detected (Table 4).…”
Section: Lignan Accumulation In Cultures Of Atma and Kt Hairy Root LImentioning
confidence: 79%
See 1 more Smart Citation
“…The results obtained in previous research performed by our group indicated that direct application of PFD to the culture system constitutes simple and efficient conditions for the enhancement of secondary metabolites production (Sykłowska-Baranek et al 2014, 2015a. In cultures of KT root line supplemented with PFD-aerated or degassed but without elicitors no lignan content was detected (Table 4).…”
Section: Lignan Accumulation In Cultures Of Atma and Kt Hairy Root LImentioning
confidence: 79%
“…PFD-aerated applied to the cell suspension cultures of Arnebia euchroma allowed to enhance naphthoquinone yield about 50% in comparison to control cultures (Sykłowska-Baranek et al 2014). The influence of PFD application at two time points: the day of inoculation (day 0) and the 14th day of culture together with elicitation (100 µM PHEN and MeJa) in ATMA transformed root cultures was studied (Sykłowska-Baranek et al 2015a).…”
Section: Lignan Accumulation In Cultures Of Atma and Kt Hairy Root LImentioning
confidence: 99%
“…by Percheron et al (1995) in the case of bacteria culture and by Sykłowska-Baranek et al (2014) in the case of plant cells) than the problem of oxygen supply. Nevertheless, accumulation of CO 2 which is gas continuously generated by cells and major waste product in culture media may cause detrimental effects in the cells, causing intracellular enzyme inhibition leading to death and further lysis of the cells.…”
Section: Pfc-mediated Transport Of Other Gasesmentioning
confidence: 99%
“…Ethene has very poor solubility in water and liquid PFC-mediated supply of this compound has great potential of applicability in plant cell cultures. Up to date the effects of ethene-saturated PFD application have been studied only in the case of submerged cultures of Arneubia euchroma cells (Sykłowska-Baranek et al, 2014) in which 26 x higher value of the ratio between alkanin/shikonin, i.e. extracellularly secreted naphtoqinone-based plant secondary metabolites, has been achieved in comparison to cultures without PFD.…”
Section: Pfc-mediated Transport Of Other Gasesmentioning
confidence: 99%
See 1 more Smart Citation